2019
DOI: 10.3390/safety5020038
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glutamine Supplement Reduces Subjective Fatigue Ratings during Repeated Bouts of Firefighting Simulations

Abstract: Wildland firefighting requires repetitive (e.g., consecutive work shifts) physical work in dangerous conditions (e.g., heat and pollution). Workers commonly enter these environments in a nonacclimated state, leading to fatigue and heightened injury risk. Strategies to improve tolerance to these stressors are lacking. Purpose: To determine if glutamine ingestion prior to and after consecutive days of firefighting simulations in the heat attenuates subjective ratings of fatigue, and evaluate if results were supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(54 reference statements)
2
3
0
Order By: Relevance
“…Due to the fact that glutamine acts as an inhibitor of prostaglandins and is widely used by lymphocytes, there can be less reduction in lymphocytes in the complement group than in the placebo group at different stages Attributed to glutamine intake. The result is consistent with the results of Mary Moore [22], Banafsheh [18], KURU et al [23]. While the result of de Siqueira research [24] showed an increase in the number of lymphocytes after taking glutamine supplementation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Due to the fact that glutamine acts as an inhibitor of prostaglandins and is widely used by lymphocytes, there can be less reduction in lymphocytes in the complement group than in the placebo group at different stages Attributed to glutamine intake. The result is consistent with the results of Mary Moore [22], Banafsheh [18], KURU et al [23]. While the result of de Siqueira research [24] showed an increase in the number of lymphocytes after taking glutamine supplementation.…”
Section: Discussionsupporting
confidence: 91%
“…Because glutamine acts as an inhibitor of prostaglandins as well as an antioxidant and fuel for immune cells, these changes can be attributed to glutamine supplementation by the experimental group. This result is consistent with the results of Mary Moore, et al [22], Jann Harberts, et al [21]. While Banafsheh [18] reported that after taking glutamine supplementation, the percentage of neutrophils in the supplement group was significantly reduced compared to the control group.…”
Section: Discussionsupporting
confidence: 91%
“…Among WFFs, two studies reported on ingestion of glutamine, an amino acid with anti‐inflammatory effects that may improve work performance. Both reported glutamine resulted in reduced subjective fatigue and improved physiologic response to heat stress compared with placebo during 2‐day firefighting simulations 89,93 . Another study demonstrated the feasibility of using wearable technology to collect typically difficult to obtain physiologic workload and productivity data from WFFs 96 .…”
Section: Resultsmentioning
confidence: 97%
“…Both reported glutamine resulted in reduced subjective fatigue and improved physiologic response to heat stress compared with placebo during 2-day firefighting simulations. 89,93 Another study demonstrated the feasibility of using wearable technology to collect typically difficult to obtain physiologic workload and productivity data from WFFs. 96 A simulation study demonstrated shortened travel distances were successful to reduce fatigue among a subgroup of WFFs (i.e., hotshot crew) who usually experience extensive travel and long work hours.…”
Section: Fatiguementioning
confidence: 99%
“…Specially, research is needed to investigate its pharmacokinetics and efficacy for guiding preventative practice before exercise in the heat, or ad-hoc medical treatment after exertional heatstroke or acute myocardial ischemia. A recent work has demonstratedHsp70 overexpression in firefighters as a result of oral glutamine ingestion (0.15 g/kg/day)11 ; further research is warranted to determine the dose-response relationship following acute and chronic supplementation. However, establishing the optimal dose of L-glutamine as a preventive measure will probably be difficult due to ethical issues and individual variability in thermotolerance or cardiac risks.…”
mentioning
confidence: 99%